Rodríguez Munguía, Jacinto. (2018) La conspiración del 68. Los intelectuales y el poder: así se fraguó la matanza, México, Debate, 338 pp. - Baltazar Mozqueda, Gerardo (2019)
Fil: Fil: Universidad Autónoma de Querétaro